Exploring the potential impact of implementing carbon capture technologies in fossil fuel power plants on regional European water stress index levels. (August 2015) - Schakel, Wouter; Pfister, Stephan; Ramírez, Andrea
Highlights: The impact of applying CCS to fossil fuel power plants on water stress in Europe is explored. CCS is not expected to increase water stress in Europe in 2030. Large scale deployment of CCS in 2050 likely to increase water stress in Europe. Increase in water stress strongly depends on technology installed. Additional research is required to further assess potential bottlenecks. Abstract: Equipping power plants with carbon capture technology can affect cooling demand and water use. This study has explored the potential impact of large scale deployment of power plants with carbon capture technologies on future regional water stress in Europe. A database including 458 of European largest power plants with data on location, technology, age, fuel type, amount of electricity generation and cooling method has been developed. This data has been combined with literature data on water use rates and developed scenarios to calculate corresponding water use of these European power plants for 2030 and 2050 under different conditions, such as the penetration level of carbon capture technologies and installed technologies. Water stress methodology based on water withdrawal has been used to explore the impact of carbon capture and storage on future water stress levels. Our findings indicate that by 2030, no considerable increase in water stress is expected due to the instalment of carbon capture technologies. However, when assuming a high penetration level of carbon capture technologies, water stress in 2050 might substantially increase in many regions in Europe. The extent of the increase in water stress strongly depends on penetration level of carbon capture, installed power plant and cooling technologies and applied water stress methodology. When using water consumption to estimate water stress, the results do not indicate significant changes in water stress for the scenarios with carbon capture. Nevertheless, as water stress based on water withdrawal is currently the common method, the results of this study provide reasons for concern regarding the potential impact of carbon capture on future European water stress levels and indicate the need for future research to monitor and possibly prevent potential water stress increases from the instalment of carbon capture technologies.